Diversity of epipelic microalgae in a shallow, tropical estuary of Northern Mindanao, Philippines - ERWIN JONES A. TUCONG; EMILIE G. TUBIO; VENUS E. LEOPARDAS (Society for Indonesian Biodiversity, 2024)
Abstract. Tucong EJA, Tubio EG, Leopardas VE. 2024. Diversity of epipelic microalgae in a shallow, tropical estuary of Northern Mindanao, Philippines. Biodiversitas 25: 3237-3245. Microphytobenthos are important primary producers in many of the most critical ecosystems, including the estuary. However, environmental variables, including season, influenced their abundance and diversity. In this study, spatial and temporal patterns of epipelic microalgae in Talabaan Estuary Naawan, Misamis Oriental, were conducted last October 2016 and February 2017 to represent wet and dry seasons, respectively. The species composition and diversity of epipelic microalgae samples were assessed using an improvised corer (2 cm, inner diameter). Only the upper 10 mm. of the cored sample was analyzed. Forty-eight species belonging to 33 families and 35 genera were identified and documented in the estuary. Diatoms (Class Bacillariophyta) were found to be the most dominant group, with about 90% of the epipelic microalgae community composed mainly of chains of cells and formed in colonies. Navicula sp. and Nitzschia sp. were among the species found in all sampled stations. The common occurrence of this species across all stations in wet and dry seasons indicated that they are the typical euryhaline species of this tropical estuary. The abundance and diversity of the epipelic microalgae community were found to vary across stations and seasons (p<0.05), but the interaction between these variables did not differ significantly. When abiotic and biological factors were regressed, a significant relationship was found with temperature, while all other factors exhibited no considerable variation. This highlights the effect of seasons in shaping benthic microalgae communities and is an essential factor in structuring microphytobenthic communities in an estuary.